Velocity measurements on a polypropylene melt during extrusion through a flat coat-hanger die - Grieß, Hans Jürgen; Burghelea, Teodor; Münstedt, Helmut (Polymer Engineering and Science, 2012)
An experimental investigation of various flow regimes observed during the extrusion of a polypropylene melt through a flat coat-hanger die by laser-Doppler velocimetry (LDV) is presented. LDV measurements of the velocity profiles across the gap of the die at various locations along the die reveal three different extrusion regimes. At small wall shear stresses, the velocity profiles can be fitted by symmetrical curves with the velocities becoming zero at the die walls. These profiles are not uniformly distributed along the die. An increase of the wall shear stress reveals a second flow regime characterized by a uniform distribution of the velocity profiles along the die. As the wall shear stress is increased even further, a third flow regime characterized by wall slip on the glass windows is observed. This flow regime is systematically characterized by measurements of the slip velocities at various temperatures and throughputs. The maximum velocities along the die are taken to assess the uniformity of flow which decisively influences the thickness of the extruded film. By measuring velocity profiles, at different throughput, and temperatures, the conditions for constant velocities along the die were determined. © 2011 Society of Plastics Engineers.
Created from Fastlane, Scopus look-up